THE COMPARISON OF MACERATION AND SOXHACLETATION METHODS EFFECTIVENESS ON GARLIC EXTRACT TO INHIBIT STAPHYLOCOCUS AUREUS GROWTH : Perbandingan Efektifitas Metode Maserasi Dan Sokletasi Pada Ekstrak Bawang Putih Terhadap Daya Hambat Staphylococus aureus - Laksmi Novrina Dewi; Hendri Poernomo; Mochammad Taha Ma’ruf (Interdental Jurnal Kedokteran Gigi (IJKG), 2022)
Introduction: An abscess is pathological, pus-filled cavity caused by mixedbacterial infection. Bacteria that a role in the process, namely Staphyloccocusaureus. Treatment of abscesses is usually by antibiotics. Abscesses caused byStaphylococcus aureus appears to be resistant to antibiotics, alternative needed by utilizing herbal plants such as garlic. Garlic has active ingredientallicin has antibacterial. Objective: The purpose was to determined whichmethod was the most effective among maceration and soxhletation methodsin making garlic extract with a concentration of 50% against the resistance ofStaphyloccocus aureus. Material and Methods: The research method usedKirby Bauer method which is sensitivity test with the agar diffusion methodusing the disc diffusion technique. The Kirby Bauer sensitivity test usingselective media, namely Muller Hinton Agar media, the inhibition zone iscreated area with a clear zone around the disc. Result: Data obtained fromthe results this study were statistically tested using normality with Shapiro-Wilk to see whether the data normally distributed or not, the expression was with the One Way Anova test to see whether there was a difference that could be measured later with the Least Significant Differencetest to see groups that are influential in inhibiting bacteria. Discussion: Thecontent of active compounds from garlic extract by soxhletation methodmore easily extracted because circulation that can increase the rate of transfercompounds from extract. Conclusion: The results, 50% concentration ofgarlic extract using the soxhletation more effective in inhibiting the growth ofStaphylococcus aureus bacteria than the maceration method.